2020
DOI: 10.1002/fes3.200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of straw returning on soil organic carbon in rice–wheat rotation system: A review

Abstract: The rice–wheat rotation model of crop planting is widely used globally, and worldwide, straw returning is the main method of crop straw treatment. However, the straw return method commonly used in the modern rice–wheat rotation system has many adverse effects on the levels and improvement of soil fertility and crop yield, and there is no systematic theory of rice and wheat straw returning to use as a guide. In this paper, we concluded that: in the rice–wheat rotation system, returning 1,500–4,500 kg/ha of rice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
100
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 199 publications
(108 citation statements)
references
References 73 publications
(77 reference statements)
6
100
1
1
Order By: Relevance
“…Returning crop residues to soil can improve soil physical properties by increasing soil moisture content, decreasing bulk density, and increasing total porosity and aggregate stability [7,27,28]. Crop residue returning can increase soil moisture content by reducing surface runoff and direct evaporation, improving soil saturated water conductivity and water infiltration [1]. Lou et al showed that straw coverage decreased the temperature of the topsoil (0-5 cm depth) and increased the soil moisture from 12.3% to 16.6% in 2008 and 2009, respectively, compared to the straw removal treatment in a 12-year maize field experiment [28].…”
Section: Texturementioning
confidence: 99%
See 2 more Smart Citations
“…Returning crop residues to soil can improve soil physical properties by increasing soil moisture content, decreasing bulk density, and increasing total porosity and aggregate stability [7,27,28]. Crop residue returning can increase soil moisture content by reducing surface runoff and direct evaporation, improving soil saturated water conductivity and water infiltration [1]. Lou et al showed that straw coverage decreased the temperature of the topsoil (0-5 cm depth) and increased the soil moisture from 12.3% to 16.6% in 2008 and 2009, respectively, compared to the straw removal treatment in a 12-year maize field experiment [28].…”
Section: Texturementioning
confidence: 99%
“…Agglomerates become larger and more stable with the crop residues inputting as the crop residues can replenish fresh organic matter to soil [34]. The proportion of soil large agglomerates and water-stabilized agglomerates reveal the sustainable capacity of soil [32].…”
Section: Texturementioning
confidence: 99%
See 1 more Smart Citation
“…Kandungan karbon organik yang tinggi pada tanah sawah dibandingkan dengan sawah reklamasi dan sawah tambang karena kandungan karbon organik tanah pada kedalaman 0 -10cm naik ketingkat tinggi dan stabil setelah 30 tahun penanaman padi (Liu et al, 2005). Tingkat akumulasi karbon orgaik yang lebih tinggi dikaitkan dengan penerapan luas pengembalian jerami padi ke lahan sawah yang menyebabkan lebih banyak input sisa padi dan mempercepat akumulasi karbon organik tanah (Jin et al, 2020). Selain peningkatan karbon organik tanah di lapisan tanah atas, kandungan bahan organik lebih tinggi di lapisan tanah bawah juga diamati lebih umum dikaitkan dengan pergerakan ke bawah sejumlah bahan organik terlarut dalam air dan karbon organik yang teradsorpsi ke partikel tanah liat (Fuhrmann et al, 2019).…”
Section: Karbon Organikunclassified
“…Rice and wheat are both important world food crops (Ladha et al, 2003), and rice–wheat rotation is one of the major food crop systems globally (Prasad, 2005), which is mainly found in East Asia and South Asia, with a cultivated area of approximately 26 million ha (Timsina & Connor, 2001), providing a stable source of food for more than 20% of the world's population (Kumari et al, 2011; Prasad, 2005). Therefore, the high and stable yields of rice–wheat rotation systems are of great impact for ensuring regional and even world food security (Jin et al, 2020). During the transition period in the modernization of agricultural production, the structure of the rural labor force changed.…”
Section: Introductionmentioning
confidence: 99%